Antes y después del terremoto y tsunami de Lima de 1746: entre la comprensión científica y los imaginarios culturales en el mundo hispano - Alvarez Ponce, Victor Emilio (2022)
On October 28, 1746, an earthquake and tsunami destroyed the viceregal city of Lima and the port of Callao. The impact of that disaster on the Hispanic world was intertwined with the advancement of science and the understanding of nature. Various proposals from a progressive and academicist clergy tried to explain these phenomena. However, the society and a traditional faction of the Church in the face of these vulnerabilities reinforced, through fear, their own mechanisms of divine protection. This article proposes a parallel development between scientific understanding and cultural imaginaries about these catastrophes in the seventeenth and eighteenth centuries in the Western world.